2017
DOI: 10.1080/10717544.2017.1282554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PEG coating on the oral bioavailability of gold nanoparticles in rats

Abstract: Metallic nanoparticles can be produced in a variety of shapes, sizes, and surface chemistries, making them promising potential tools for drug delivery. Most studies to date have evaluated uptake of metallic nanoparticles from the GI tract with methods that are at best semiquantitative. This study used the classical method of comparing blood concentration area under the curve (AUC) following intravenous and oral doses to determine the oral bioavailability of 1, 2 and 5 kDa PEG-coated 5 nm gold nanoparticles (Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…The results of this in vivo study showed that both TGNPs and LTGNPs have an improved curative effect and low toxicity, and the synergistic effect produced by LTGNPs can improve the properties of the particles. 117 Alalaiwe et al conducted a test in order to evaluate the quantitative oral bioavailability of PEG-coated GNPs in rats by measuring the concentration of gold in the blood, liver, spleen, and kidneys of rats at different time intervals after oral administration of a certain dose of GNPs; 118 however, this classical approach to analyze bioavailability needs more studies. In recent years, hyperthermia and photodynamic therapy have received considerable attention, and numerous studies have shown their great potential for cancer treatment.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…The results of this in vivo study showed that both TGNPs and LTGNPs have an improved curative effect and low toxicity, and the synergistic effect produced by LTGNPs can improve the properties of the particles. 117 Alalaiwe et al conducted a test in order to evaluate the quantitative oral bioavailability of PEG-coated GNPs in rats by measuring the concentration of gold in the blood, liver, spleen, and kidneys of rats at different time intervals after oral administration of a certain dose of GNPs; 118 however, this classical approach to analyze bioavailability needs more studies. In recent years, hyperthermia and photodynamic therapy have received considerable attention, and numerous studies have shown their great potential for cancer treatment.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…The intravenous and oral doses study shows the bioavailability of 1, 2 and 5 kDa PEG-coated 5 nm gold nanoparticles (AuNPs) in male rats. The oral dose revealed the highest concentrations of NP in kidneys and similar concentrations in different organs on intravenous doses (Alalaiwe et al, 2017). Our study revealed AuNP intravenous administration has no toxicity in the organs of rats, which supports the practice of biofunctionalized AuNP with further detail molecular study for the treatment and drug delivery in diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Gold nanoparticles of approximately 3 nm were fabricated by the method reported elsewhere (Alalaiwe et al, 2017). The nanoparticles, which formed rapidly upon addition of the sodium borohydride, were then allowed to stand overnight prior to coating.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously investigated the oral bioavailability of gold nanoparticles in rats, wherein, gold nanoparticles of approximately 5 nm were coated with 1, 2 and 5 kDa of polyethylene glycol (PEG) (Alalaiwe et al, 2017). PEG coating was supposed to enhance the oral bioavailability of the nanoparticles as it known to minimize the immune system recognition and elimination, thereby increasing circulatory half-life (Alalaiwe et al, 2017). Furthermore, PEG coating has also been reported to minimize the agglomeration of nanoparticles (Hinkley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%